It is not all about salary: a discrete-choice experiment to determine community health workers’ motivation for work in Nigeria - David Peiris; Blake Angell; Rohina Joshi; Seye Abimbola; Azeb Gebresilassie Tesema; Whenayon Simeon Ajisegiri; Olumuyiwa O Odusanya (BMJ Global Health, 2022)
Introduction Community health workers (CHWs) constitute the majority of primary healthcare (PHC) workers in Nigeria, yet little is understood about their motivations or the most effective interventions to meet their needs to ensure quality health coverage across the country. We aimed to identify factors that would motivate CHWs for quality service delivery.Methods A discrete-choice experiment was conducted among 300 CHWs across 44 PHC facilities in the Federal Capital Territory, Abuja Nigeria. Based on the literature review and qualitative research, five attributes, namely: salary, educational opportunities, career progression and in-service training, housing and transportation, were included in the experiment. CHWs were presented with 12 unlabelled choice sets, using tablet devices, and asked to choose which of two hypothetical jobs they would accept if offered to them, or whether they would take neither job. Mixed multinomial logistic models were used to estimate stated preferences for the attributes and the likely uptake of jobs under different policy packages was simulated.Results About 70% of the respondents were women and 39% worked as volunteers. Jobs that offered career progression were the strongest motivators among the formally employed CHWs (β=0.33) while the ‘opportunity to convert from CHW to another cadre of health workers, such as nursing’ was the most important motivator among the volunteers’ CHWs (β=0.53). CHWs also strongly preferred jobs that would offer educational opportunities, including scholarship (β=0.31) and provision of transport allowances (β=0.26). Policy scenario modelling predicted combined educational opportunities, career progression opportunities and an additional 10% of salary as incentives was the employment package that would be most appealing to CHWs.Conclusion CHWs are motivated by a mix of non-financial and financial incentives. Policy interventions that would improve motivation should be adequate to address various contexts facing different CHWs and be flexible enough to meet their differing needs.